2022
DOI: 10.3390/ijgi11050299
|View full text |Cite
|
Sign up to set email alerts
|

Digital Soil Mapping of Soil Organic Matter with Deep Learning Algorithms

Abstract: Digital soil mapping has emerged as a new method to describe the spatial distribution of soils economically and efficiently. In this study, a lightweight soil organic matter (SOM) mapping method based on a deep residual network, which we call LSM-ResNet, is proposed to make accurate predictions with background covariates. ResNet not only integrates spatial background information around the observed environmental covariates, but also reduces problems such as information loss, which undermines the integrity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…In the validation analysis, the SOM map showed reliable results, with R 2 = 0.61, MAPE = 41.18%, and RMSE = 2.03%. When compared to previous studies, we can observe that the general level of validation accuracy for SOM predictions ranges between R 2 = 0.45 at 10 m using topographic attributes only [70], R 2 = 0.51 at 30 m [71], and R 2 = 0.53 using a QRF at 30 m resolution [34]. In our study, the observed standard deviation of the prediction distribution ranged from 1.7% to 7.7%.…”
Section: Discussionsupporting
confidence: 51%
“…In the validation analysis, the SOM map showed reliable results, with R 2 = 0.61, MAPE = 41.18%, and RMSE = 2.03%. When compared to previous studies, we can observe that the general level of validation accuracy for SOM predictions ranges between R 2 = 0.45 at 10 m using topographic attributes only [70], R 2 = 0.51 at 30 m [71], and R 2 = 0.53 using a QRF at 30 m resolution [34]. In our study, the observed standard deviation of the prediction distribution ranged from 1.7% to 7.7%.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, climate-related covariates which focus on climatic factors were found in 8% of the reviewed articles. These covariates were recognized for their significance in shaping soil properties, especially in lowlands with diverse climatic conditions [35,49,62]. They play a critical role in assessing soil resilience to climate change and its implications for sustainable land use and agriculture.…”
Section: Environmental Covariates For Dsm In Lowland Areasmentioning
confidence: 99%
“…Second, the residual block structure in the ResNet network enhanced the depth of the model network. This enabled the model to learn the characteristics of the spectral curve more deeply, while avoiding model instability and accuracy loss caused by increased network depth [66,67]. Third, in the establishment of the weighted layer, we used the MSE with the largest subset of 1600 times for modeling, removed frequency bands with smaller MSE coefficients, and used the normalized absolute value of the MSE coefficient as the initial weight.…”
Section: Cnn Modeling Based On Resnetmentioning
confidence: 99%